2019
DOI: 10.1039/c9dt01018a
|View full text |Cite
|
Sign up to set email alerts
|

4-Halo-1,2,3-triazolylidenes: stable carbenes featuring halogen bonding

Abstract: Synthesis and coordination of 4-halo-1,2,3-triazolylidenes have been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 80 publications
0
24
0
Order By: Relevance
“…XB acceptor centers conventionally include electronegative hetero-atoms bearing lone pair(s) with many elements, such as halogens 8 , chalcogens 9 , pnictogens 10 etc., electrondonating π-systems, and even electron-donating positively charged metal centers 11,12 . Carbon-the structural core of all organic matter, the element that gives the highest diversity of compounds, their forms, and covalent bonds-is involved in noncovalent interactions as XB acceptor mostly as part of a πsystem (e.g., double-bonded 13 , triple-bonded 14 , or aromatic systems 15 ). The solid-state interaction involving the carbon lone pair (lp) and halogen atom has been previously observed in only one case, namely in the adduct (IAd)•IPFB formed upon the interplay of iodopentafluorobenzene (IPFB) and N-heterocyclic carbene (IAd) 16 .…”
mentioning
confidence: 99%
“…XB acceptor centers conventionally include electronegative hetero-atoms bearing lone pair(s) with many elements, such as halogens 8 , chalcogens 9 , pnictogens 10 etc., electrondonating π-systems, and even electron-donating positively charged metal centers 11,12 . Carbon-the structural core of all organic matter, the element that gives the highest diversity of compounds, their forms, and covalent bonds-is involved in noncovalent interactions as XB acceptor mostly as part of a πsystem (e.g., double-bonded 13 , triple-bonded 14 , or aromatic systems 15 ). The solid-state interaction involving the carbon lone pair (lp) and halogen atom has been previously observed in only one case, namely in the adduct (IAd)•IPFB formed upon the interplay of iodopentafluorobenzene (IPFB) and N-heterocyclic carbene (IAd) 16 .…”
mentioning
confidence: 99%
“…Recently, we found that 4-iodotriazolylidene can be prepared by the treatment of a 4,5-unsubstituted triazolium salt with one equivalent I 2 in the presence of two equivalents of potassium tert-butoxide [43]. When 4,5-unsubstituted triazolium salt 1 was treated with two equivalents I 2 and two equivalents of potassium tert-butoxide, 4,5-diiodo-1,3-dimesityl-1,2,3-triazolium 2-I was synthesized in a good yield (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…1,2,3-Triazoles and 1,2,3-triazolium-based XB activators have been found applications in catalytic reactions [40,41] and anion recognition [42]. Recently, we reported neutral 4-halo-1,2,3-triazolylidenes C [43], which had a carbene character with σ-donation at the carbon and a σ-hole at the halogen atom. XB is observed by single-crystal X-ray diffraction in their coinage metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that a weaker donor would lead to a relative upfield shift, whereas a stronger donor would lead to a downfield shift of the HEP signal. Different types of NHCs, phosphines, isocyanides, and N‐donors have been evaluated . Furthermore, much smaller electronic differences among similar ligands can be resolved, providing useful information for the fine‐tuning of complexes.…”
Section: Introductionmentioning
confidence: 95%
“…Different types of NHCs, [6] phosphines, isocyanides, and N-donors have been evaluated. [7][8][9][10] Furthermore,m uch smaller electronic differences among similar ligands can be resolved, providing useful information for the fine-tuning of complexes.…”
Section: Introductionmentioning
confidence: 99%